Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0269215519862328
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the psychometric properties of patient-reported outcome measures for rheumatoid arthritis in the foot and ankle

Abstract: Objective: To identify self-reported outcome measures specific to the foot and ankle in patients with rheumatoid arthritis and to investigate the methodological quality and psychometric properties of these measures. Method: A systematic review focusing on patients with rheumatoid arthritis. Setting: The search was conducted in the PubMed, SCOPUS, CINAHL, PEDro and Google Scholar databases, based on the following inclusion criteria: population (with rheumatoid arthritis) > 18 years; psychometric or clinimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…On the other hand, foot pain was not correlated to structural damage [6]. Multiple patient-reported outcome measures were developed to evaluate foot function in RA [7]. The Rheumatoid and Arthritis Outcome Score (RAOS) is an adaptation of the Knee Injury and Osteoarthritis Outcome Score [8], and is intended to evaluate symptoms and functional limitations of people with chronic inflammatory joint diseases and problems from lower extremities induced by treatment (medication, operation, physical therapy).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, foot pain was not correlated to structural damage [6]. Multiple patient-reported outcome measures were developed to evaluate foot function in RA [7]. The Rheumatoid and Arthritis Outcome Score (RAOS) is an adaptation of the Knee Injury and Osteoarthritis Outcome Score [8], and is intended to evaluate symptoms and functional limitations of people with chronic inflammatory joint diseases and problems from lower extremities induced by treatment (medication, operation, physical therapy).…”
Section: Resultsmentioning
confidence: 99%
“…It is to mention that assessing gait speed alone was found equivalent to the use of the whole Short Physical Performance Battery (Guralnik et al., 2000). Besides, a systematic review evaluating the psychometric properties of patient‐reported outcome measures for RA with foot and ankle involvement showed positive evidence for the RAOS for its content validity, internal consistency, reproducibility, and reliability (Ortega‐Avila et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…7 10-12 Various systematic reviews have been published to help select the most appropriate PROM with the best evidence, however, these are frequently associated with a single domain or specific joints. [13][14][15][16] Given the substantial number of domains that could be considered, and their associated PROMs, a catalogue of available PROMs across all relevant domains should be of value. Consequently, the current EULAR funded study, aimed to review all available PROMs used in RA, together with their performance metrics to help make informed choices about the most appropriate PROM for a given purpose.…”
Section: What Does This Study Add?mentioning
confidence: 99%